As Catequistas Franciscanas - a antecipação do aggiornamento em Santa Catarina - de Lurdes Gascho, Maria (1997)
This article entitled “Franciscan Catechists – na anticipation of the aggiornamento the State of Santa Catarina” (Catequistas Franciscanas - a antecipação do aggiornamento em Santa Catarina) deals with the journey of a religious congregation which was founded in 1915 in Santa Catarina. The reason of this foundation was to be in attendance the concrete problems of the people and respond to local challenges. The way of life of the members of the congregation took original and creative forms, outside of the model prescribed for the religion’s life of the period. They were know amidst the people as “masters” and differed in their way of life from the nuns who followed the model of life prescribed and approved by the Catholic Church.